The Potential Risk of Electronic Waste Disposal into Aquatic Media: The Case of Personal Computer Motherboards - Georgios Kalamaras; Maria Kloukinioti; Maria Antonopoulou; Ioanna Ntaikou; Dimitris Vlastos; Antonios Eleftherianos; Stefanos Dailianis (Toxics, 2021)
Considering that electronic wastes (e-wastes) have been recently recognized as a potent environmental and human threat, the present study aimed to assess the potential risk of personal computer motherboards (PCMBs) leaching into aquatic media, following a real-life scenario. Specifically, PCMBs were submerged for 30 days in both distilled water (DW) and artificial seawater (ASW). Afterwards, PCMBs leachates were chemically characterized (i.e., total organic carbon, ions, and trace elements) and finally used (a) for culturing freshwater (Chlorococcum sp. and Scenedesmus rubescens) and saltwater (Dunaliella tertiolecta and Tisochrysis lutea) microalgae for 10 days (240 h), (b) as the exposure medium for mussel Mytilus galloprovincialis (96 h exposure), and (c) for performing the Cytokinesis Block Micronucleus (CBMN) assay in human lymphocytes cultures. According to the results, PCMBs could mediate both fresh- and marine algae growth rates over time, thus enhancing the cytotoxic, oxidative, and genotoxic effects in the hemocytes of mussels (in terms of lysosomal membrane impairment, lipid peroxidation, and NO content and micronuclei formation, respectively), as well as human lymphocytes (in terms of MN formation and CBPI values, respectively). The current findings clearly revealed that PCMBs leaching into the aquatic media could pose detrimental effects on both aquatic organisms and human cells.